APLIKASI EVALUASI KERUSAKAN JEMBATAN BETON BERBASIS SISTEM PAKAR DENGAN TEKNOLOGI ANDROID - Sofa Marwoto (Jurnal Riset Rekayasa Sipil, 2019)
Bridges are a part of transportation infrastructure that has a vital role in connecting separated places separated by natural geographical conditions. Periodical evaluation/investigation the existing condition of the bridge is very necessary to be done because the load passing over the bridge today tends to increase due to community activities. Expert system is one of the artificial intelligence technologies that aims to help the user in solving problems that require expert expertise in the field in accordance with the problem at hand. By entering data into the system, the user will get a solution related to the problem at hand. The study discusses the use of Android-based smartphone technology to implement expert systems in applications aimed at evaluating the extent of damage to concrete bridges. This research was conducted by making an expert system model which is implemented into an application using android technology (Android Studio). The resulting Android application is used to capture visual damage data of the concrete bridge. This application offers convenience and flexibility in its application because its mobility.